Sub-picosecond exchange–relaxation in the compensated ferrimagnet Mn2RuxGa. (29th January 2021) - Bonfiglio, G; Rode, K; Atcheson, G Y P; Stamenov, P; Coey, J M D; Kimel, A V; Rasing, Th; Kirilyuk, A
Abstract: We study the demagnetization dynamics of the fully compensated half-metallic ferrimagnet Mn2 Ru x Ga. While the two antiferromagnetically coupled sublattices are both composed of manganese, they exhibit different temperature dependencies due to their differing local environments. The sublattice magnetization dynamics triggered by femtosecond laser pulses are studied to reveal the roles played by the spin and intersublattice exchange. We find a two-step demagnetization process, similar to the well-established case of Gd(FeCo)3, where on a 5 ps timescale the two Mn-sublattices seem to have different demagnetization rates. The behaviour is analysed using a four-temperature model, assigning different temperatures to the two manganese spin baths. Even in this strongly exchange-coupled system, the two spin reservoirs have considerably different behaviour. The half-metallic nature and strong exchange coupling of Mn2 Ru x Ga lead to spin angular momentum conservation at much shorter time scales than found for Gd(FeCo)3 which suggests that low-power, sub-picosecond switching of the net moment of Mn2 Ru x Ga is possible.